Perspective Taking and Empathy: Does Having Similar Past Experience to Another Person Make It Easier to Take Their Perspective?. (1st September 2015) - Gerace, Adam; Day, Andrew; Casey, Sharon; Mohr, Philip
Abstract : This study tested the hypothesis that it is easier to take the perspective of another person when one has similar past experience. Volunteer participants ( N = 154) were asked to take the perspective of a protagonist in one of four problematic interpersonal situations and then to rate the ease with which they felt able to perspective take and the extent of their personal past experience of similar situations. Similar past experience predicted ease of perspective taking, with the relationship influenced by reflection on past experience. Ease of perspective taking mediated the relationship between similar past experience and participant perceptions of their accuracy in understanding the other person, but ease was not associated with emotional arousal. The findings have potential therapeutic applications for attempts to increase empathy and understanding in people for whom perspective taking may be difficult.